Metadiscursive markers in the context of Italian migration in Germany: an intergenerational perspective - De Marco, Anna; Palumbo, Mariagrazia (Cuadernos de Filología Italiana, 2022)
he present study investigates the use of Discourse Markers (DMs) in the context of Italian migration varieties using an onomasiological approach, i.e. looking at the functions that DMs entail in conversation. Thus, this study focuses on intergenerational variation, namely, how the use of DMs in terms of their functional space varies across generations. We will consider only the metadiscoursive functions, i.e. all the microfunctions aiming at structuring the discourse, ensuring clarity and affecting the organization of discourse. They are analysed in two generations of Italian migrants living in Munich. Data are taken from a corpus of audio recorded interview with 13 Italian migrants living in Munich (average length of each interview, 30 minutes). Results point out that the second-generation informants DMs undergo both a gradual loss of types and a gradual reduction of tokens.